2020
DOI: 10.3389/fmicb.2020.00213
|View full text |Cite
|
Sign up to set email alerts
|

SPT20 Regulates the Hog1-MAPK Pathway and Is Involved in Candida albicans Response to Hyperosmotic Stress

Abstract: Candida albicans is the most common fungal pathogen and relies on the Hog1-MAPK pathway to resist osmotic stress posed by the environment or during host invasions. Here, we investigated the role of SPT20 in response to osmotic stress. Testing a C. albicans spt20 / mutant, we found it was sensitive to osmotic stress. Using sequence alignment, we identified the conserved functional domains between CaSpt20 and ScSpt20. Reconstitution of the Spt20 function in a spt20 /CaSPT20 complemented strain found CaSPT20 can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…We found that conditional mutants spt7 and spt8 were filamentous and invasive in both filamentous inducing and non-inducing conditions while tra1Δ and ngg1Δ were in a yeast-locked state compared to wild type. As well, similar to spt3Δ/Δ and spt20Δ/Δ deleted strains in C. albicans ( Laprade et al, 2002 ; Wang et al, 2020 ), we found cells of the spt7 and spt8 conditional mutants did not separate properly during cell division and appeared clumped together. Also, the spt7 and spt8 repressed mutants formed wrinkled colonies in both inducing and non-inducing conditions—indication of filamentous cells, while the ngg1 and tra1 repressed mutants formed smooth colonies even in the hyphal-inducing conditions of either 10% fetal calf serum (FCS) or Spider media at 37°C for 5 days when compared to the wild type CaSS1 strain (data not shown).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We found that conditional mutants spt7 and spt8 were filamentous and invasive in both filamentous inducing and non-inducing conditions while tra1Δ and ngg1Δ were in a yeast-locked state compared to wild type. As well, similar to spt3Δ/Δ and spt20Δ/Δ deleted strains in C. albicans ( Laprade et al, 2002 ; Wang et al, 2020 ), we found cells of the spt7 and spt8 conditional mutants did not separate properly during cell division and appeared clumped together. Also, the spt7 and spt8 repressed mutants formed wrinkled colonies in both inducing and non-inducing conditions—indication of filamentous cells, while the ngg1 and tra1 repressed mutants formed smooth colonies even in the hyphal-inducing conditions of either 10% fetal calf serum (FCS) or Spider media at 37°C for 5 days when compared to the wild type CaSS1 strain (data not shown).…”
Section: Resultssupporting
confidence: 78%
“…In S. cerevisiae , the HOG1 pathway controls the synthesis and storage of glycerol which increases intracellular osmotic/turgor pressure to allow cells adapt to high osmotic environments ( Saito and Tatebayashi, 2004 ). Mutations that affect SAGA structural integrity play a critical role for survival at high osmolarity ( Daniel and Grant, 2007 ): the HOG1 MAP kinase pathway recruits SAGA and promotes RNA polymerase II binding to initiate transcription ( Proft and Struhl, 2002 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of L. angustifolia free and liposome-encapsulated oil on the expression of ERG 11 , ALS 5 , HOG 1 and CDR1 ( Table S1 ) [ 39 , 40 ] in persister-derived biofilms of C. auris was analysed using qRT—PCR. Briefly, persister-derived biofilms were treated with 0.05% v / v oil or liposome-encapsulated oil for 24 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…There are many conditions in which glycerol concentration can increase. Firstly, glycerol is produced and accumulated in cultures and conditions where there is osmotic or citric acid stress -a response mediated via the Hog1 MAPK (high osmolarity glycerol 1 mitogen activated protein kinase) pathway (39,40). We observed during culture that cells were not well suspended in wells.…”
Section: Discussionmentioning
confidence: 92%